ANALISIS FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP HARGA SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Agung Jati Kusuma, 08.05.52.0117; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2016)
This study aims to determine the influence of Current Ratio (CR), Debt To Equity Ratio (DER), Return on Equity (ROE), and Retun On Asset (ROA), on stock prices of companies included kategorProperty and Real Estate listed on the Indonesia Stock Exchange (IDX) The population is all companies Property and Real Estate in the Indonesia Stock Exchange (IDX) with a number of 50 companies and research over the period 2011 to 2013. The sample in this study is much 43 companies. The sampling technique used was purposive sampling. The analytical tool used in this research is Multiple Regression Analysis. The results showed that the coefficient of determination in this study is the value of Adjusted R Square of 57.5%. As for the statistical test F-test shows that, antaraCurrentRatio (CR), Debt To Equity Ratio (DER), Return on Equity (ROE) and Return on Assets (ROA), jointly affect the price stock. And partial hypothesis testing results show that there is positive Return On Equity (ROE) on stock prices. While untukCurrent Ratio (CR), Debt To Equity Ratio (DER), Return on Assets (ROA), indicates there is a negative effect on stock prices. Keywords : Current Ratio (CR) , Debt To Equity Ratio (DER), Return On Equity (ROE), Return On Assets (ROA), Stock Price